Shoreline Dynamics Along a Developed River Mouth Barrier Island: Multi-Decadal Cycles of Erosion and Event-Driven Mitigation - Hein, Christopher J.; Fallon, Andrew R.; Rosen, Peter; Hoagland, Porter; Georgiou, Ioannis Y.; FitzGerald, Duncan M.; Morris, Michael; Baker, Sarah; Marino, George B.; Fitzsimons, Gregory (Frontiers in Earth Science, 2019)
Human modifications in response to erosion have altered the natural transport of sediment to and across the coastal zone, thereby potentially exacerbating the impacts of future erosive events. Using a combination of historical shoreline-change mapping, sediment sampling, three-dimensional beach surveys, and hydrodynamic modeling of nearshore and inlet processes, this study explored the feedbacks between periodic coastal erosion patterns and associated mitigation responses, focusing on the open-ocean and inner-inlet beaches of Plum Island and the Merrimack River Inlet, Massachusetts, USA. Installation of river-mouth jetties in the early 20th century stabilized the inlet, allowing residential development in northern Plum Island, but triggering successive, multi-decadal cycles of alternating beach erosion and accretion along the inner-inlet and oceanfront beaches. At a finer spatial scale, the formation and southerly migration of an erosion “hotspot” (a setback of the high-water line by ~100 m) occurs regularly (every 25–40 yr) in response to the refraction of northeast storm waves around the ebb-tidal delta. Growth of the delta progressively shifts the focus of storm wave energy further down-shore, replenishing updrift segments with sand through the detachment, landward migration, and shoreline-welding of swash bars. Monitoring recent hotspot migration (2008–2014) demonstrates erosion (>30,000 m3 of sand) along a 350-m section of beach in six months, followed by recovery, as the hotspot migrated further south. In response to these erosion cycles, local residents and governmental agencies attempted to protect shorefront properties with a variety of soft and hard structures. The latter have provided protection to some homes, but enhanced erosion elsewhere. Although the local community is in broad agreement about the need to plan for long-term coastal changes associated with sea-level rise and increased storminess, real-time responses have involved reactions mainly to short-term (<5 yr) erosion threats. A collective consensus for sustainable management of this area is lacking and the development of a longer-term adaptive perspective needed for proper planning has been elusive. With a deepening understanding of multi-decadal coastal dynamics, including a characterization of the relative contributions of both nature and humans, we can be more optimistic that adaptations beyond mere reactions to shoreline change are achievable.